The Performance Of Islamic Banking Based On Sharia Maqashid Index (SMI) - Suci Aprilliani Utami; Yana Rohmana; Firmansyah Firmansyah; Ripan Hermawan (Universitas Pendidikan Indonesia, 2021)
AbstractPurpose – The purpose of the study must be stated in abstract. Ideally in one sentence, the primary objectives should be clear. This section also contains scope of the study or the reasons why the paper was conducted.Methodology - An abstract of a scientific work may include specific models or approaches used in the larger study. Other abstracts may describe the types of evidence used in the research. The methodology used in the paper should be presented clearly. Findings - The abstract must be written in English. The abstract should be in one paragraph with no more than 250 words. It uses Times New Roman 11, single space, and italic. The abstract should contain purpose, methodology, findings, novelty, research limitation, research implication, keywords, and paper type. Novelty – The paper should have originality or novelty. This term means something completely different. To a researcher and a funding source, a novel idea means something that is unique in the field or scope being analyzed. It can be a new methodology or a new design that sets the stage for new knowledge. Research Limitation - The weaknesses of the study, often outside of control of the researcher should be written in this study. These could include things like time, access to funding, equipment, data or participants.Research Implication - How does this work add to the body of knowledge on the topic? Are there any practical or theoretical applications from your findings or implications for future research?Keywords: It is a maximum of 5 keywords in English with apparent meaning. The keywords are separated by a semicolon (;). For example, Islamic bank; profit sharing; customer satisfaction.